Manajemen Kurikulum Dan Pembelajaran Bahasa Arab(Studi Situs Di Mts Ppmi Assalaam Surakarta) - Syakir, Ahmad, Prof. Dr. Sutama, M.Pd (2016)
This study aimed to describe the preparation of curriculum, teaching staff, the implementation of learning the Arabic language and Arabic language curriculum evaluation. The research method used descriptive qualitative approach. Data collection techniques of observation, interviews, documentation, to test the validity of the data using triangulation sources, methods, time. The results of this study (1) the preparation of the Arabic language curriculum beginning the preparation of the annual program, the semester program as a reference cornerstone in the implementation of learning and preparation of syllabus and lesson plans for teachers' reference in the classroom. (2) Preparation of teaching staff and the administration of the test conducted specific tests that a written test, an oral, teaching Arabic language and preferred alumni of the boarding school, have a good character and loyal. Increased competence seminars, study permit training in or outside the cottage. (3) The implementation of learning the Arabic language based learning components to equip the Arabic language skills are an active and well maharatul qiroah kalam, kitabah, simaah and were able to examine examines al-Quran as-sunah, books of scholars and be positive the importance of studying the Arabic language. Learning methods lectures, discussion, qowaid, direct method, as well as a laboratory practicum language. Instructional media used textbooks, whiteboard, laptop, slide and language laboratory. Evaluation of learning with pretest and post-test on the learning formative and sumative (4) Evaluation of Arabic language curriculum implemented but not yet optimal